2016
DOI: 10.36685/phi.v2i3.81
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Marketing Mix and Patient Loyalty in Intensive Care Unit, Anutapura Public Hospital Palu

Abstract: Background: The problem generally faced by hospital is unable to provide something really needed by the customers. One of the main factors is the poor marketing mix of hospital that impacts to low quality and influences the patients loyality.Objective: The research aims to investigate the relationship between marketing mix and patient loyalty in intensive care unit at Anutapura Public Hospital Palu.Methods: This was a cross sectional study involving 97 persons who were randomly selected without considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The service process is a series of procedures, a routine mechanism in which a service is delivered to consumers. 11 By holding a process of handling health problems, supporting services and administrative services that are fast, efficient and optimal so that they can support the products/services they sell. The researcher believes that the Haji Makassar Hospital has paid attention to the standard aspects of health services provided to all visiting patients, one of which can be seen starting from registration if the patient does not understand, visitors can ask the officer directly and then the officer will direct what services will be needed.…”
Section: The Influence Of the Process On Patient Satisfaction With Ty...mentioning
confidence: 99%
“…The service process is a series of procedures, a routine mechanism in which a service is delivered to consumers. 11 By holding a process of handling health problems, supporting services and administrative services that are fast, efficient and optimal so that they can support the products/services they sell. The researcher believes that the Haji Makassar Hospital has paid attention to the standard aspects of health services provided to all visiting patients, one of which can be seen starting from registration if the patient does not understand, visitors can ask the officer directly and then the officer will direct what services will be needed.…”
Section: The Influence Of the Process On Patient Satisfaction With Ty...mentioning
confidence: 99%
“…Aditi at al (2019) found that service, price promotion, and brand equity together have a positive significant effect on customers preference (Aditi & Muda, 2019). Napira et al (2016) found a significant relationship between price and patient brand loyalty (Napirah, Rau, & Hadijah, 2016).…”
Section: Service Marketing MIX Elementsmentioning
confidence: 99%